Osmoprotectants content, ascorbic acid and ascorbate peroxidase on bean leaves under drought stress - Agricolas, Ciencias (Revista Mexicana de Ciencias Agrícolas, 2018)
The accumulation of osmoprotectants in plants that are under stress from drought, allow you to offset the negative effect that causes these environmental conditions. In this study the biochemical response of bean plants based on the accumulation of soluble carbohydrates, starch, ascorbic acid, and the activity of ascorbate peroxidase enzyme, simple leaves and the first two leaves trifoliolate of studied resistant variety, Pinto Villa, and susceptible to drought Bayo Madero, both of Durango race. Plants from two varieties were subjected to three moisture treatments, irrigation and irrigation drought recovery. Regarding Bayo Madero, Pinto Villa showed increased stress tolerance response related humidity: high concentrations of proline, ascorbic acid, and increased activity of the peroxidase enzyme ascorbate, the latter in the drying treatment. In relation to the amount of soluble carbohydrates, Bayo Madero was statistically superior (p< 0.05) to Pinto Villa, which may indicate that these compounds are being used by the plant to synthesize other compounds as osmoprotectants proline and which can be regarded as indicators important to classify plant species to survive and fulfill their life cycle under conditions of moisture stress.